1999
DOI: 10.1038/sj.leu.2401462
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated responsiveness to transforming growth factor-β is correlated with functional differences between human adult and fetal primitive hematopoietic progenitor cells

Abstract: Important functional differences exist between primitive CD34 ++ CD38 − hematopoietic progenitor cells derived from human fetal liver (FL) and adult bone marrow (ABM). FL progenitors are known to have higher proliferative capacities and lower cytokine requirements than their ABM counterparts. In this study, we isolated FL and ABM CD34 ++ CD38 − cells and used a two-stage culture system to investigate the effects of transforming growth factor-␤ (TGF-␤) and blocking anti-TGF-␤ antibodies (anti-TGF-␤) on these ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This discrepancy may be due to the fact that different culture conditions induce the proliferation of divergent cell populations. It is also possible that the primitive hemopoietic progenitor cells from different sources may behave differently in response to TGF-␤ signaling and signaling of the other cytokines (40). The third possibility is that overexpression of T␤RIIDN blocks the signaling of all TGF-␤ isoforms, whereas the Ab or antisense oligonucleotide based approach may only block the signaling of one TGF-␤ isoform.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be due to the fact that different culture conditions induce the proliferation of divergent cell populations. It is also possible that the primitive hemopoietic progenitor cells from different sources may behave differently in response to TGF-␤ signaling and signaling of the other cytokines (40). The third possibility is that overexpression of T␤RIIDN blocks the signaling of all TGF-␤ isoforms, whereas the Ab or antisense oligonucleotide based approach may only block the signaling of one TGF-␤ isoform.…”
Section: Discussionmentioning
confidence: 99%
“…Early hematopoietic progenitors normally produce TGFb (Majka et al, 2001) that can act in an autocrine fashion (Batard et al, 2000), and neutralization of TGFb by monoclonal antibodies has been reported to recruit early progenitors into the cell cycle and induce them to dierentiate (Batard et al, 2000;Dao et al, 1998;Ducos et al, 2000;Pierelli et al, 2000;Weekx et al, 1999). Lineagerestricted progenitor cells are generally less responsive to growth inhibition by TGFb (Cashman et al, 1999, Sargiacomo et al, 1991, although some eects on apoptosis and dierentiation have been observed (Cashman et al, 1999;Dybedal et al, 1997).…”
Section: Insensitivity To Antiproliferative Signalsmentioning
confidence: 99%
“…Cells in newly formed blastocysts are initially resistant to TGFß, but later in development, cells acquire TGFß sensitivity [31]. Moreover, the basis for TGFß-resistance by mouse embryonic stem cells is lack of RII receptors and corresponding absence of Smad 2 nuclear localization [33].…”
Section: Discussionmentioning
confidence: 99%
“…Fetal liver progenitor cells are also TGFß-resistant [33] and clusters of cells in primary fetal hepatocyte cultures have been shown resistant to differentiation by EGF and TGFß [27]. Thus, adifferentiation may be a general property of stem and progenitor cells, whether embryonic or adult; and reduced or absent RII expression may be the molecular basis.…”
Section: Discussionmentioning
confidence: 99%